Implementasi Media Padlet pada Pembelajaran TIK dalam Meningkatkan Motivasi Belajar Siswa Kelas IX SMPN 1 Munjungan - Mahendro, Gogor; Budi Lestari, Purwaning; Asih Wahyu Hartati, Tri (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This research aims to increase students' learning motivation in ICT learning using Padlet media. This type of research is Classroom Action Research which consists of 2 cycles. The subjects of this research were 32 class IX students of SMPN 1 Munjungan Trenggalek. The results of the research show that there has been an increase in the implementation of padlet media in ICT materials at SMPN 1 Munjungan. The percentage in cycle 1 was 64% and increased in cycle 2 by 80.5%. Next, there are 6 indicators of learning motivation that are studied. Six indicators experienced an increase in the percentage of each indicator from cycle 1 to cycle 2. The conclusion of this research is that the implementation of Padlet media in ICT materials can increase student learning motivation.